Considerations on the role of creatine on physical performance - Francisco Leonardo Torres-Leal; Dilina do Nascimento Marreiro (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p294 Creatine, a nitrogenous compound found mainly in food of animal origin, has been used as an ergogenic supplement with the aim of improving performance in physical exercise. The objective of this review is to provide up-todate information about aspects related to creatine metabolism and its role in physical performance. Indexed articles from the Pubmed, Scielo and Lilacs database were analyzed, preference being given to randomized placebo-controlled trials. Previous research has suggested that creatine supplementation may increase muscular concentration of this compound either in its free or phosphorylated form, enhancing performance in high-intensity, short-duration activities. The mechanisms involved in the storage of creatine have not been completely elucidated. Several studies have shown promising results regarding creatine supplementation in sports that require a single high intensity and/or short-term effort. In this context, the biochemical interactions related to the action of creatine in performance improvement are not clear. Further studies into the role of this compound in reactions involved in the storage and production of energy may lead to a better understanding of energy metabolism in physical performance. This knowledge could then guide other experimental tests to establish creatine's ergogenic potential as a strategy for performance improvement.